KAED ICT labs utilization performance for teaching and learning: Semester 2 of 2016/2017 Vs. Semester 1 of 2016/2017; Semester 1 And 2 of 2015/2016 - Ayob, Mohd Fairullazi (2017)
This report is prepared and tabled in Kulliyyah meeting with the objective to update and improve the utilization of ICT labs for teaching and learning programmes